The Phenomenon of Father's Involvement in Stimulating Gross Motor Development Children Aged 3-6 Years in The Family Environment Pacitan City - Endah Wahyu Sugiharti; Rita Wahyu Utami; Abdullah Aziz Assa'diy (Journal of Innovative and Creativity, 2025)
Gross motor development in early childhood is an important aspect that forms the foundation of physical and cognitive abilities. The process of stimulating growth and early childhood development requires support from both parents. This proves that the parenting process requires cooperation between mothers and fathers in order to produce good stimulation for children's growth and development. This study aims to describe and analyze the phenomenon of father's involvement pattern in providing gross motor stimulation and forms of stimulation provided as well as the perspective of parents regarding this role in the family environment. This study uses descriptive qualitative with a case study method. The subjects of the study were 15 parents who had children aged 3-6 years in the Pacitan City area using the purposive sampling technique. Data were collected through participatory observation, in-depth interviews and documentation of father-and-son play activities. Data analysis is carried out through data reduction, data presentation and conclusion drawn. The results of the study showed that the intense physical involvement of the father such as throwing and catching the ball and activities outside the house were specifically the main characteristics of the stimulation given by the father. Dominant fathers use a challenging, low-risk, and interactive style of play. It has been shown to be effective in spurring coordination of movement and the strength of children's large muscles. Most parents have a positive view of the involvement of fathers in having a significant impact on increasing confidence, courage in taking risks, gross motor maturity of children and complementing the role of mothers which focus more on fine motor activities and child care. The conclusion of this study is that strengthening the role of a father in providing gross motor stimulation for children aged 3-6 years needs to be a special concern in early childhood parenting education.